Endocrine Effects of Coffee Consumption - YAVUZ, DİLEK; APAYDIN, TUĞÇE (TURKIYE KLINIKLERI, 2020)
Caffeine has been found to exert various biological effects including, antiangiogenic, antiproliferative, antimetastatic activity, increased fat oxidation and mobilization of glycogen in muscle, increased lipolysis, and reduction of body fat. The aim of this review is to analyze the endocrine effects of coffee consumption. A systematic literature search was conducted on PubMed and Web of Science databases seeking articles published until May 2019, dealing with coffee consumption and diabetes, osteoporosis, thyroid gland, adrenal, and gonads. The results of the most epidemiologic studies reported that coffee consumption has positive effects on combating type 2 diabetes risk, has no significant effects on bone mineral density levels but fracture risk was shown to be higher in the high coffee consumer group. Coffee intake has no significant effect on thyroid cancer, increases sex hormone binding globulin levels, has no effect on fertility but higher consumption was related to spontaneous abortion. Studies pertaining to coffee consumption and endocrine effects have contrary results. More randomized clinical studies with a long term follow up period are required.
Keywords: Coffee; diabetes mellitus; fertility; onadal hormones; osteoporosis; hyroid diseases; TYPE-2 DIABETES-MELLITUS; BONE-MINERAL DENSITY; HORMONE-BINDING GLOBULIN; CAFFEINE CONSUMPTION; POSTMENOPAUSAL WOMEN; CIGARETTE-SMOKING; SEMEN QUALITY; DECAFFEINATED COFFEE; TEA CONSUMPTION; RISK-FACTORS